Natural mixing behaviour of waste rocks poured in a paste backfill - Zhang, Y.; Li, L. (Paste 2023: Proceedings of the 25th International Conference on Paste, Thickened and Filtered Tailings, 2023)
In underground mines, large quantities of waste rock can be produced during development in order to access ore bodies. The waste rock is typically hoisted to the surface and transported to a specific place to make a structure called a waste rock pile. This practice requires energy consumption and generates additional operating costs for transporting waste rock from underground to the surface. Alternatively, the waste rock can be poured directly into underground mine stopes filled with paste backfill. As a result, energy consumption and additional operating costs for transporting the waste rock from underground to the surface are avoided or significantly reduced. However, the natural mixing behaviour of waste rocks poured in paste backfill has never been studied. The fill mass generated by this practice can fail and collapse upon a side-exposure associated with the excavation of an adjacent stope if a poor mixture between the cohesionless waste rocks and cemented paste backfill takes place around the exposed face. Thus, it is critical to understand the mixing behaviour of waste rocks poured in paste backfill. To this end, a series of physical model tests have been performed in the laboratory. The results, in part, are presented and discussed in this paper.